2015
DOI: 10.1094/pdis-02-15-0236-re
|View full text |Cite
|
Sign up to set email alerts
|

Anastomosis Groups and Pathogenicity ofRhizoctonia solaniand BinucleateRhizoctoniafrom Potato in South Africa

Abstract: A survey of anastomosis groups (AG) of Rhizoctonia spp. associated with potato diseases was conducted in South Africa. In total, 112 Rhizoctonia solani and 19 binucleate Rhizoctonia (BNR) isolates were recovered from diseased potato plants, characterized for AG and pathogenicity. The AG identity of the isolates was confirmed using phylogenetic analysis of the internal transcribed spacer region of ribosomal DNA. R. solani isolates recovered belonged to AG 3-PT, AG 2-2IIIB, AG 4HG-I, AG 4HG-III, and AG 5, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 31 publications
4
48
0
Order By: Relevance
“…Within the same AG, Muzhinji, Truter, Woodhall, and van der Waals (2015) determined that the virulence may vary from one isolate to another isolate, which had consistency with the present study. Their study also showed that BN Rhizoctonia AG-R isolates were more virulent in causing stem canker and black scurf on potato than that of AG-A.…”
Section: Discussionsupporting
confidence: 87%
“…Within the same AG, Muzhinji, Truter, Woodhall, and van der Waals (2015) determined that the virulence may vary from one isolate to another isolate, which had consistency with the present study. Their study also showed that BN Rhizoctonia AG-R isolates were more virulent in causing stem canker and black scurf on potato than that of AG-A.…”
Section: Discussionsupporting
confidence: 87%
“…The AG identity of the isolates was confirmed by DNA sequencing of the internal transcribed spacer region (ITS) as described in a separate study (Muzhinji et al 2015). Soil-borne inoculum was prepared according to the method of Atkinson et al (2010) homogenized by blending in 4 L of sterile water into slurry, mixed with 10 L of vermiculite and incubated for five weeks with shaking after every two days.…”
Section: Inoculum Preparationmentioning
confidence: 99%
“…Rhizoctonia diseases on stems and stolons were presented as a disease index (DI). Disease index for stems and black scurf were calculated as described previously (Muzhinji et al 2015).…”
Section: Inoculum Preparationmentioning
confidence: 99%
See 2 more Smart Citations